Psychological Flexibility and Self-Compassion as Predictors of Well-Being: Mediating Role of a Balanced Time Perspective - Pyszkowska, Anna; Rönnlund, Michael (Frontiers in Psychology, 2021)
Measures of psychological flexibility and self-compassion are strongly associated with well-being. The aim of the present study was test the hypothesis that these relationships are mediated by a balanced time perspective, a proposed ideal way of relating to the past, present, and future that may correspond with an ability to flexibly switch temporal focus. For this purpose, a Polish community sample (N = 421) responded to a web-survey including measures of psychological flexibility (AAQ-II), self-compassion (SCS), two measures of positive aspects of well-being (Satisfaction with Life, Quality of Life), and the Zimbardo Time Perspective Inventory (ZTPI). Structural equation models, involving a measure of deviation from a balanced time perspective (DBTP) as a mediator of relationships between latent-level psychological flexibility, self-compassion and well-being factors, were tested. We examined separate models for psychological flexibility and self-compassion and a model including both constructs. The results for separate models were consistent with partial mediation of relationships with well-being, both for psychological flexibility and self-compassion. Results for the analysis involving both constructs, suggested unique contributions of both to DBTP, which in turn predicted well-being, but the link between psychological flexibility and DBTP appeared to be the strongest. In further analyses, three ZTPI dimensions were identified as most critical, namely Past Positive, Present Fatalistic, and Past Negative, each of which were part of an indirect effect on well-being. Psychological flexibility in particular, showed a strong negative association with a Past Negative orientation. Taken together, the results indicate that time perspective is a factor to understand the links between psychological flexibility/self-compassion and well-being. While the results pertaining to self-compassion were consistent with results of a couple of prior studies, this is, to our knowledge, the first demonstration of a link between psychological flexibility and a balanced time perspective. These findings should be relevant for clinical research and practice.